Transcriptomic and metabolomic insights into temperature-dependent changes in catechin and anthocyanin accumulation in tea plants with different leaf colors - Jingbo Yu; Qianying Wang; Wenli Wang; Ruihong Ma; Changqing Ding; Kang Wei; Liyuan Wang; Shibe Ge; Yuanzhi Shi; Xin Li (Plant Stress)
Tea (Camellia sinensis) is a globally important cash crop, with a variety of kinds depending on colors and constituents. Temperatures influence leaf color and secondary metabolite accumulation in tea plants and thus it is worth investigating global metabolic and transcriptomic changes in different tea cultivars under different temperature regimes. In this study, the dynamic changes in key genes and secondary metabolites were analyzed in the purple-leaf tea cultivar ‘Zijuan’ (ZJ) and the green-leaf cultivar ‘Longjing 43’ (LJ) under four temperature conditions (15 °C, 20 °C, 25 °C, and 35 °C), employing RNA-sequencing and targeted metabolomics (UPLC-GC/MS). Results showed that anthocyanin content in ZJ was significantly higher at 15 °C and 20 °C than at 25 °C and 35 °C, suggesting that low temperatures strongly enhance anthocyanin synthesis. In contrast, LJ exhibited greater catechin accumulation at lower temperatures, especially at 15 °C and 20 °C, where the relative content of key compounds was significantly higher than at 25 °C. Low temperatures enhanced the expression of ANTHOCYANIDIN SYNTHASE (ANS) in ZJ while inhibiting the expression of ANTHOCYANIDIN REDUCTASE (ANR) and LEUCOANTHOCYANIDIN REDUCTASE (LAR). Nonetheless, all three genes were suppressed by high temperatures in ZJ. In LJ, the expression of ANS, ANR, and LAR showed similar trends under both low and high temperatures, suggesting that the metabolic responses to temperature changes are more consistent in LJ. Weighted gene co-expression network analysis (WGCNA) identified key transcription factors that are significantly positively correlated with catechin and anthocyanin accumulation, including bHLH (CSS0002807), NAC (CSS0035736), AP2/ERF (CSS0000647), MYB (CSS0000220), MYB (CSS0002706), and WRKY (CSS0024910). Overall, this study provides novel insights into the secondary metabolite response mechanisms of tea plants under different temperatures and offers theoretical support for the breeding and selection of new tea cultivars.